Karl von Holteis Kościuszko-Verehrung - Połczyńska, Edyta (Studia Germanica Posnaniensia, 2018)
The article deals with the subject within studies on motives and problems of Poland in German literature. It describes the origin of the drama about Tadeusz Kościuszko “Der alte Feldherr” [The Old Leader] by the German playwright and novalist Karl von Holtei. At the same time it reflects repercussions which were caused by the staging of the "Old Leader" in 1825 in Königstädter Theater in Berlin. Karl von Holtei who was himself an actor, practised mostly a rare profession of a declaimer, played many times the role of Tadeusz Kościuszko, contributing for its popularity. In his autobiography “Vierzig Jahre” [Forty Years] Holtei says, when describing his life full of travels, that it was the spirit of Kościuszko which made him a constant wonderer. The article traces the truthfulness of his words.